Outcome of patients with proximal vessel occlusion of the anterior circulation and DWI-PWI mismatch is time-dependent - Mundiyanapurath, Sibu; Diatschuk, Sascha; Loebel, Sarah; Pfaff, Johannes; Pham, Mirko; Möhlenbruch, Markus Alfred; Wick, Wolfgang; Bendszus, Martin; Ringleb, Peter A.; Radbruch, Alexander (European journal of radiology, 2017)
Background and purpose Patients with ischemic stroke and large vessel occlusion are assumed to benefit from endovascular therapy (ET) independent of the symptom onset-to-treatment time (OTT) if they present with a mismatch of diffusion- and perfusion-weighted imaging (DWI-PWI mismatch). We aimed at studying the influence of OTT on clinical outcome in these patients. Methods Retrospective database review in a tertiary care university hospital. All patients presented with proximal vessel occlusion of the anterior circulation and DWI-PWI mismatch. Primary outcome was the influence of OTT on modified Rankin scale (mRS) score three months after treatment, dichotomized in favourable (0-2) and unfavourable outcome (3-6). Secondary outcome was the effect of OTT on the shift of the mRS score. Patients treated within an early time window (<340min) and a late time window (≥340min) were compared. Results 139 patients were included. The rate of favourable outcome was significantly higher in patients who were treated in an early compared to those treated in a late time window (31 [49%] vs. 20 patients [27%], p=0.005). Adjusted multivariate logistic regression revealed that late treatment was an independent negative predictor of favourable outcome (odds ratio 0.39, confidence interval [0.18-0.84]; p=0.016). A shift towards higher mRS scores for late treatment was evident (p=0.015). In sensitivity analysis, OTT remained an independent predictor when evaluated as continuous variable. These findings were confirmed in patients with a comparable DWI-PWI mismatch according to the definitions from large trials (DEFUSE 2, DEFUSE 3, SWIFT-PRIME, EXTEND-IA). Conclusion Outcome of patients with comparable DWI-PWI mismatch is time-dependent.